Single-drop microextraction - Tang, Sheng; Qi, Tong; Ansah, Prince Dim; Nalouzebi Fouemina, Juliette Chancellevie; Shen, Wei; Basheer, Chanbasha; Lee, Hian Kee (TrAC, Trends in analytical chemistry (Regular ed.), 2018)
After its introduction just over twenty years ago, single-drop microextraction (SDME) became a widely applied solvent-based microextraction procedure as a practical sample preparation tool in support of chemical and biological, food, pharmaceutical, clinical and forensic analysis. In general, SDME is inexpensive, easy to operate, nearly solvent-free, and can be conducted using very basic apparatus. It can be used to realize high analyte enrichment in a relatively short time, and be easily combined with various instrumental techniques (e.g., GC-MS, HPLC-UV) for analysis. Recently, continuing strong interest in SDME has spawned new developments such as its implementation in microfluidic chip technologies, and operational processes (e.g., new devices, automation), engagement with materials chemistry (e.g., nanomaterials), and, of course, an expanding range of applications. In this review, we present a short historical overview of SDME, and then focus on its most recent (ca. 2017-2018) developments and advances. Future trends are also discussed and predicted. •A historical account of single-drop microextraction is given.•The most recent SDME developments are reviewed.•Future trends and directions are discussed.•Discussions are mainly centred on devices, materials, processes and applications.